ANALISIS POTENSI MIKRO HIDRO UNTUK MENUNJANG PARIWISATA BERKELANJUTAN DI DESA LES - Putra Winaya, Ida Bagus; Putri Siswanto, Fagita; Guna Winangun, Nyoman Gede Resa; Gunantara, Nyoman; Sukerayasa, I Wayan; Arsa Suyadnya, I Made (Jurnal SPEKTRUM, 2024)
Les Village in Tejakula District, Buleleng Regency, Bali, has appealing natural tourism potential, particularly Les Waterfall. One of the potentials of Les Waterfall is the water flow that can be harnessed as a renewable energy source. This potential can support sustainable tourism in Les Village through the planning of a Micro Hydropower Plant (PLTMH), which will later be used for lighting at the waterfall tourist site. This research involves measuring the head, water flow velocity, and water discharge as parameters to determine the type of waterwheel. Additionally, the study measures the power output and rotational speed of the waterwheel to identify the appropriate generator type. The findings from this research demonstrate that the potential Micro Hydropower Plant in the tourist area of Les Village can generate up to 0.449 kW using an Undershot waterwheel and a PMG type GDF-100 generator.